2006
DOI: 10.1271/bbb.60081
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Calcium Signaling Pathways inL-Leucine-Stimulated Protein Synthesis in L6 Myotubes

Abstract: L-Leucine is known to stimulate protein synthesis in L6 myotubes. In the present study, we examined the possible involvement of calcium signaling pathways in the stimulation of protein synthesis induced by L-leucine in L6 myotubes. After 16 h of treatment with L-leucinedepleted medium, the re-addition of L-leucine for 4 h augmented protein synthesis by about 50% as compared with an L-leucine-depleted control. Ryanodine receptor antagonists almost completely abolished the stimulatory effect of L-leucine, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The positive effects of L‐Leu supplementation on protein synthesis have been widely studied in situations where the subjects were either in deficient or fasting conditions,8, 11, 12, 13, 14, 15 and therefore under a catabolic stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive effects of L‐Leu supplementation on protein synthesis have been widely studied in situations where the subjects were either in deficient or fasting conditions,8, 11, 12, 13, 14, 15 and therefore under a catabolic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…L-Leu stimulates protein synthesis in muscle cells through at least two distinct mechanisms: by stimulation of mRNA translation initiation machinery 13,35 and by activation of intracellular signalling pathways linked to mTOR. 6,36,37 The positive effects of L-Leu supplementation on protein synthesis have been widely studied in situations where the subjects were either in deficient or fasting conditions, 8,[11][12][13][14][15] and therefore under a catabolic stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Raffaello, Mammucari, Gherardi, & Rizzuto, 2016). Miura et al (2006) recently observed in L6 myotubes that leucine stimulated protein synthesis was inhibited by ryanodine receptor antagonist or 2-APB, an IP 3 receptor antagonist. In our conditions, neither ryanodine nor 2-APB were able to prevent the rimonabant-induced protein synthesis in C2C12 myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…L6 myoblasts established from rat skeletal muscle tissues are well known to grow rapidly, fuse spontaneously, differentiate into multinucleated myotubes [5], and are widely used in the studies on the effects of various biofactors on muscle functions in vitro. The stimulatory effect of leucine on protein synthesis has been demonstrated in differentiated L6 myocytes (myotubes) [6,7] through several signaling pathways. Leucine has been also demonstrated to stimulate glucose uptake (GU) in the soleus muscle of rats [8].…”
Section: Introductionmentioning
confidence: 99%